Boundaries between parties and the academy. Ethnographic approach to the educational plateau of Flamenco dance in Seville, Spain and Merida, Yucatan - Pérez Antúnez, Cynthia Jeannette (IE Revista de Investigación Educativa de la REDIECH, 2021)
Flamenco dance is a cultural manifestation directly associated with Andalusia, Spain. However, especially since the second half of the 20th century, it has been practiced in different parts of the world, in such a way that even UNESCO declared it an Intangible Cultural Heritage of Humanity in 2010. In my anthropological doctoral research, I approached Flamenco dance from a performative methodology for field work and from the theoretical perspective of rhizome for analysis. I settled in two places mainly: Seville, Spain, and Merida, Yucatan. The teaching-learning processes of Flamenco dance turned out to be as different as these cities each other. In this article I present an ethnographic dialogue with the different educational experiences I had access to in both contexts explored. I speak of the transmission of Flamenco dance knowledge through schools in different modalities, starting from an axis with two opposite poles between the party and the academy.